Therapeutic effects of allopurinol on the function of left ventricular and activity of matrix metalloproteinase enzymes (MMPs) in patients with chronic heart failure: Therapeutic effects of Allopurinol on left ventricular and MMPs - Deng, Hua; Li, Qiaolian; Zhu, Dan (Cellular and Molecular Biology, 2022)
Heart failure is a growing public health problem, especially in the elderly, often occurring due to ischemia and coronary artery disease. Allopurinol can protect against myocardial ischemia and improve myocardial energy utilization during ischemia. On the other hand, matrix metalloproteinase (MMP) enzymes play an essential role in causing atherosclerosis, obstruction, and myocardial infarction. Therefore, in the present study, the effect of allopurinol on the function of the left ventricular and the activity of MMP-1, MMP-2, MMP-3, and MMP-9 were evaluated in heart failure patients. In this clinical trial, 82 patients were randomly assigned to allopurinol or placebo in addition to standard treatment. Echocardiographic evaluations were performed before treatment and six months after treatment. Also, after allopurinol treatment, plasma and peripheral blood mononuclear cells were extracted from control and intervention groups. The active form of MMPs was measured by ELISA and mRNA expression by Real-time PCR. The rate of change in left ventricular ejection fraction in the allopurinol group was significantly higher than patients in the control group. There was also found more improvement in NYHA class in patients receiving allopurinol than in the control group. ELISA results showed that all plasma MMP levels in the control group were significantly higher than those in the allopurinol group (P<0.001). Quantitative determination of mRNA expression in MMPs by Real-time RT-PCR revealed that, except for MMP-9, there was no significant difference in the expression of evaluated MMPs between the treatment and control groups. In general, the results showed that long-term administration of allopurinol improves left ventricular function, and it has beneficial effects on the life quality of patients with heart failure.